Digital crowdfunding for waqf-based forest carbon projects: A model for strengthening inclusive and sustainable Islamic green finance - Nadhrah Ilmina Dilsyaadi; Faizatul Maghfirah; Muhammad Wildan (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The transition toward a green economy has intensified the demand for sustainable and ethically grounded financing models to support forest conservation and climate mitigation, particularly in countries with high deforestation pressure such as Indonesia. While voluntary carbon markets provide a mechanism to value ecosystem services, their financing structures remain dominated by conventional approaches and have rarely incorporated Islamic social finance instruments. This study aims to assess the feasibility of integrating waqf-based forest conservation with Sharia-compliant digital crowdfunding and voluntary carbon trading to support environmental sustainability and community empowerment. Method: This study employs a qualitative exploratory approach using semi-structured interviews with nine key stakeholders, including waqf managers, Sharia regulators, forestry practitioners, Islamic finance professionals, and green finance academics. Data were collected purposively and analyzed through thematic analysis to identify patterns related to opportunities, challenges, and model feasibility. Findings: The findings indicate that waqf-based forest projects hold strong potential across social, economic, and ecological dimensions by enabling community participation, generating diversified income from non-timber forest products and carbon credits, and contributing to carbon sequestration and biodiversity conservation. Sharia-compliant crowdfunding enhances inclusivity and transparency in waqf fundraising; however, its effectiveness depends on regulatory clarity, institutional capacity of waqf managers, digital literacy, and public trust. Major challenges include regulatory fragmentation, the absence of specific Sharia guidance on carbon-related assets, and financial risks arising from high upfront costs and uncertain carbon revenues. The results demonstrate consistency between the proposed model and the principles of sustainable development and Islamic objectives emphasizing public benefit and environmental stewardship. Conclusion: The study concludes that the integrated model is feasible for phased implementation under clear regulatory, institutional, and Sharia governance frameworks. Novelty/Originality of this article: This article contributes a novel Islamic green finance framework by empirically validating an integrated model that links waqf forest financing, Sharia-compliant crowdfunding, and voluntary carbon markets.